PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING DENGAN MEDIA VISUAL DALAM MEMAHAMI KONSEP MATEMATIKA - Syahmudi Louk; Yuan Andinny; Ihwan Zulkarnain (Prodi Pendidikan Matematika FKIP Universitas Madura, 2019)
The aim of this study is to differ the Creative Problem Solving learning model and the Constructivism learning model in understanding mathematical concepts. This research was conducted at PB Islamic High School. Soedirman Cijantung East Jakarta precisely in class X. The research method used to test these differences is the quasi-experimental method. Population of class X students of Islamic High School PB. Soedirman Cijantung used as a sample of 54 students, with the sampling technique used is cluster random sampling. The research instrument used was a test ability to understand mathematical concepts in the form of a description of 10 questions that had been tested previously. Based on the results of the analysis and discussion, then in this study it can be concluded that based on the analysis with the t-test, t_count> ttable is obtained. From the test results obtained the ability to understand mathematical concepts using the Creative Problem Solving learning model is higher than the Constructivism learning model. So it can be concluded that there is a different effect between the application of the Creative Problem Solving learning model and the Constructivism learning model on the ability to understand mathematical concepts.